2010
DOI: 10.1103/physrevb.81.224520
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic superconducting properties of single-crystallineFeSe0.5Te0.5

Abstract: Iron-chalcogenide single crystals with the nominal composition FeSe0.5Te0.5 and a transition temperature of Tc14.6 K were synthesized by the Bridgman method. The structural and anisotropic superconducting properties of those crystals were investigated by means of single crystal x-ray and neutron powder diffraction, superconducting quantum interference device and torque magnetometry, and muon-spin rotation (SR). Room temperature neutron powder diffraction reveals that 95% of the crystal volume is of the same te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
136
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 137 publications
(193 citation statements)
references
References 81 publications
43
136
5
Order By: Relevance
“…The zero temperature values of the energy gaps ∆ I (0) and ∆ II (0) are 2.5 meV (∆ I (0)/k B T c = 1.93) and 1.1 meV (∆ II (0)/k B T c = 0.9), respectively. From the previous measurements, such as µSR 32,33 and penetration depth, 24 two isotropic gaps were reported with gap values similar to our results. µSR studies in FeSe 0.5 Te 0.5 [32 and 33] revealed two gaps of ∆ large ∼ 2.6 meV and ∆ small ∼ 0.5-0.87 meV, and the penetration depth study 24 also showed that ∆ large ∼ 2.1 meV and ∆ s ∼ 1.2 meV.…”
Section: 25supporting
confidence: 79%
“…The zero temperature values of the energy gaps ∆ I (0) and ∆ II (0) are 2.5 meV (∆ I (0)/k B T c = 1.93) and 1.1 meV (∆ II (0)/k B T c = 0.9), respectively. From the previous measurements, such as µSR 32,33 and penetration depth, 24 two isotropic gaps were reported with gap values similar to our results. µSR studies in FeSe 0.5 Te 0.5 [32 and 33] revealed two gaps of ∆ large ∼ 2.6 meV and ∆ small ∼ 0.5-0.87 meV, and the penetration depth study 24 also showed that ∆ large ∼ 2.1 meV and ∆ s ∼ 1.2 meV.…”
Section: 25supporting
confidence: 79%
“…We estimate from the crystal dimensions the approximate demagnetization factors anisotropy at low temperatures is estimated to be ∼ 2.8, which is in good agreement with previous reports [38,39]. Since according to [40] ( 1) it is possible to estimate the penetration depths being equal to λ ab ≈ 250 nm and λ c ≈ 970 nm, invoking the coherence lengths of ξ ab ≈ 4 nm and ξ c ≈ 0.8 nm estimated by the resistivity measurements discussed below. indicate an increase in the effectiveness of pinning centers giving rise to a "peak effect".…”
Section: Magnetic Properties Of Prfeasosupporting
confidence: 77%
“…A two-gap scenario is in line with the generally accepted view of multi-gap superconductivity in Fe-based HTS. 5,6,8,[27][28][29] The magnitudes of the large and the small gap for Ba 1−x Rb x Fe 2 As 2 (x = 0.3, 0.35, 0.4) (see Table I) are in good agreement with the results of a previous report. 5 There it was pointed out that most Fe-based HTS's exhibit two-gap superconducting behavior, characterized by a large gap with 2∆/k B T c = 7(2) and a small one with 2.5(1.5).…”
supporting
confidence: 82%